2014
DOI: 10.1063/1.4875535
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs tunnel diodes for the calibration of semi-classical and quantum mechanical band-to-band tunneling models

Abstract: Promising predictions are made for III-V tunnel-field-effect transistor (FET), but there is still uncertainty on the parameters used in the band-to-band tunneling models. Therefore, two simulators are calibrated in this paper; the first one uses a semi-classical tunneling model based on Kane's formalism, and the second one is a quantum mechanical simulator implemented with an envelope function formalism. The calibration is done for In 0.53 Ga 0.47 As using several pþ/intrinsic/nþ diodes with different intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…1(a). Calibrated simulations showed that an In 0.5 Ga 0.5 As homojunction line-TFET can achieve I on ¼ 200 mA/mm 2 for V dd ¼ 0.5 V which is significantly better than for Silicon TFET [4]. Nevertheless, different material systems with even higher BTBT generation rates are desirable to further improve electrical performances with higher boost I on and lower SS.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…1(a). Calibrated simulations showed that an In 0.5 Ga 0.5 As homojunction line-TFET can achieve I on ¼ 200 mA/mm 2 for V dd ¼ 0.5 V which is significantly better than for Silicon TFET [4]. Nevertheless, different material systems with even higher BTBT generation rates are desirable to further improve electrical performances with higher boost I on and lower SS.…”
Section: Introductionmentioning
confidence: 93%
“…In this vein, we have recently proposed a BTBT measurement method using highly doped Esaki tunnel diodes as a simple way to have an accurate device prediction [4]. This way, besides the complex TFET device fabrication, the high-k/semiconductor interface problems are avoided.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This competition of factors can be better observed using numerical simulations, using an Sentaurus Device simulator [38]. The simulations were performed for a uniform In 0.53 Ga 0.47 As channel device, considering dopant-dependent SRH, Schenk's non-local TAT, non-local BTBT, and bandgap narrowing models, which parameters where obtained in [39]. Figure 8 presents the simulated I DS as a function of V GS , separating the influence of the thermally activated mechanisms (TAT and SRH) and BTBT.…”
Section: Introductionmentioning
confidence: 99%
“…Diodes with junction areas A j ¼ 0.01-2 lm 2 are fabricated according to the process flow in Ref. 21. We measure the diode I-V characteristics with an Agilent 4156C parameter analyzer.…”
mentioning
confidence: 99%